Controlling Calcium Oxalate Crystal Growth Using Pectin and Sodium Alginate Natural Polymers - AL-Dubai, Ahmed; Akyol, Emel (WILEY-V C H VERLAG GMBH, 2024)
Calcium oxalate (CaOx) crystallization is a common phenomenon that contributes to various kidney disorders and stone formation, as well as the formation of scale in industrial processes. The inhibition of CaOx is an area of intense scientific interest in the field of materials science due to its relevance to biomineralization. The present study investigated the effects of pectin (PE) and sodium alginate (SA), two natural polymers, on the growth of CaOx crystals using a batch crystallization method in aqueous solutions at 37 degrees C with different concentrations (0.5, 1, 5, and 10 ppm). The results of the study showed that both PE and SA were effective inhibitors of CaOx crystal growth, with the highest inhibition observed at a concentration of 10 ppm, reaching 80 %. PE did not significantly affect the size of the crystals, while SA reduced their size as the concentration increased. These findings contribute to our understanding of the potential of natural polymers as non-toxic inhibitors of CaOx crystal growth. This study explores the inhibitory effects of natural polymers, pectin and sodium alginate, on calcium oxalate crystal growth. Using a batch crystallization method at 37 degrees C with varying concentrations, results demonstrate significant inhibition, highlighting the potential of these polymers as non-toxic inhibitors in medical and industrial applications. image
Keywords: Calcium oxalate crystal; Inhibition; Natural polymer; Pectin; Sodium alginate; IN-VITRO; CRYSTALLIZATION; KINETICS; AGGREGATION; MONOHYDRATE; MORPHOLOGY; DIHYDRATE; ADHERENCE; PROTEIN; Engineering